Numerical Study on the Reduction of Dynamic Lateral Earth Pressure on Retaining Wall using Waste Tyre. Issue 1 (1st January 2023) - Singh, Vikash; Bano, Samreen; Kumar, Rakesh; Tripathi, Vivek Kumar; Verma, Anand
Abstract: The performance of retaining under various loading circumstances is dependent on the kind of backfills employed; nonetheless, several lightweight fill materials such as EPS geofoam, geoboard, fly ash, waste tyre (in various forms), and so on are widely utilised as backfill materials. The key benefits of adopting lightweight materials are a lower overall lateral force on the wall and lateral displacement of the retaining wall. Because of the growing number of automobiles, disposing of discarded tyres has become a major issue. Waste tyres are increasingly being utilised in geotechnical applications such as embankment fill, retaining walls, machine foundations, and bridge abutments. According to prior research, shredded tyre inclusion with soil is employed as backfill material for earth-retaining constructions. The most important aspect of sectional design for retaining walls is the total lateral thrust. Literature indicates that the use of waste tyres in backfill decreases the overall lateral thrust whether used as sole backfill as tyre chips or a mixture of sand tyres or when used as a compressible inclusion between the wall and the backfill. In the present work, a numerical simulation was conducted using OPTUM G2 (a computational tool based on finite elements) to examine the effect of discarded tyres as backfill material on the total lateral earth pressure for an 8-meter-high wall. Maximum surcharge pressure of 20 kPa is applied to the backfilling. The use of discarded tyres as a backfill material significantly decreases total lateral earth pressure on the wall by 50-54% compared to walls backfilled with soil, according to the current study.